Potato yield empowerment by photosynthesis, carbon assimilation, and evapotranspiration - Neofytou, Eleni; Neophytides, Stelios; Tsoumas, Ilias; Tsalakou, Andria; Christoforou, Michalakis; Eliades, Marinos; Papoutsa, Christiana; Kontoes, Charalampos; Hadjimitsis, Diofantos G. (My University, 2024)
By the end of the twenty-first century, atmospheric CO2 is expected to have increased from its current level of approximately 400 μmol CO2 mol−1 to approximately 700 μmol CO2 mol−1. A significant rise in atmospheric CO2 concentration could have a global impact on crop output, photosynthetic efficiency, and plant development. The majority of C3 plant species will be benefited by the predicted rise of the atmospheric CO2 concentration, especially through increased rates of photosynthesis and water use efficiency (WUE), which could ultimately improve plant biomass and yield. Potatoes are considered the world’s most popular non-cereal food in terms of global food security. Water stress has a significant impact on photosynthesis. Water deficit can prevent CO2 absorbance from leaves and/or interfere with mesophyll cells' capacity to carboxylate CO2, negatively affecting photosynthesis. Water shortage can lead to partial or whole leave stomata closure reducing the transpiration rates leading to low photosynthetic rate. Since potatoes are cultivated in a variety of climates, it's critical to comprehend how photosynthetic rate, gross primary productivity as a proxy of soil organic carbon, and actual evapotranspiration are correlated with yield productivity. In this study, satellite products of NASA’s MODIS are derived to gather the needed observations and a regression analysis is performed to identify the relations between yield and natural processes.
Keywords: yield; irrigation; natural processes; earth observation; correlation analysis